Behaviour and residual compression resistances of circular high strength concrete-filled stainless steel tube (HCFSST) stub columns after exposure to fire - He, An (2022)
The structural behaviour and residual compression resistances of circular high strength concrete-filled stainless steel tube (HCFSST) stub columns after exposure to fire were experimentally and numerically investigated in this paper. The experimental study was performed on 12 circular HCFSST stub column specimens after exposure to the ISO-834 standard fire for three levels of heating durations (15 min, 30 min and 45 min) as well as 4 unheated circular HCFSST stub column specimens (i.e. reference specimens). The experimental study was supplemented by a numerical modelling study, where two types of finite element (FE) models, namely heat transfer and mechanical FE models, were firstly developed to simulate the thermal and mechanical responses of the circular HCFSST stub column specimens, and then used to perform parametric studies to derive additional numerical results. Due to the lack of existing design codes for concrete-filled stainless steel tube members and concrete-filled carbon steel tube members after exposure to fire, the corresponding codified design provisions for circular concrete-filled carbon steel tube members at room temperature, as established in Europe, Australia and America, were evaluated for their suitability to circular HCFSST stub columns after exposure to fire, based on the test and numerical parametric study results. It was generally found that both the European and Australian codes yield a high level of accuracy and consistency in predicting the residual compression resistances of circular HCFSST stub columns after exposure to fire, while the American specification leads to rather conservative and scattered design residual compression resistances.